Lycopodium japonicum Thunb. inhibits chondrocyte apoptosis, senescence and inflammation in osteoarthritis through STING/NF-κB signaling pathway - Ma, Jiawei; Zhang, Hanwen; Wang, Ze; Xu, Cong; Tan, Hongye; Sun, Yun; Zheng, Rukang; Jin, Zebin; Li, Yuanyuan; Ge, Xinjiang; Wu, Yaosen; Zhou, Yifei (Journal of ethnopharmacology, 2024)
Osteoarthritis (OA) is a degenerative disease, its characteristic lies in the inflammation and extracellular matrix (ECM) degradation, can lead to significant personal disability and social burden. Lycopodium japonicum Thunb. (LJT) is a lycopinaceae plant with anti-inflammatory and analgesic effects. In traditional Oriental medicine, LJT is commonly used to treat a variety of conditions, including osteoarthritis and low back pain. To investigate the anti-apoptotic, anti-inflammatory and anti-senescence properties of LJT in IL-1β-induced mouse chondrocytes, and to clarify the underlying mechanisms involved. In addition, the study also examined the effects of LJT by establishing a mouse model of osteoarthritis. The ultimate goal is to identify the mechanism of LJT as an anti-osteoarthritis agent. In this research, molecular docking and network pharmacology analysis were performed to identify the latent pathways and key targets of LJT action. The CCK-8 kit was used to evaluate LJT's effect on chondrocyte viability. Western blotting, Immunofluorescence, TUNEL staining kit, and SA-β-gal staining were employed to verify LJT's impact on chondrocytes. Additionally, SO, HE, and Immunohistochemical were utilized to assess LJT's effects on osteoarthritis in mice. In vitro and in vivo experiments were performed to verify the potential mechanism of LJT in OA. Network pharmacology analysis revealed that AKT1, PTGS2, and ESR1 were the key candidate targets for the treatment of OA with LJT. The results of molecular docking indicated that AKT1 exhibited a low binding affinity to the principal constituents of LJT. Hence, we have chosen STING, an upstream regulator of PTGS2, as our target for investigation. Molecular docking revealed that sitosterol, formononetin, stigmasterol and alpha-Onocerin, the main components of LJT, have good binding activity with STING. In vitro experiments showed that LJT inhibited IL-1β-mediated secretion of inflammatory mediators, apoptosis and senescence of chondrocytes. The results showed that LJT abolished cartilage degeneration induced by unstable medial meniscus (DMM) in mice. Mechanism research has shown that LJT by inhibiting the STING/NF-κB signaling pathways, down-regulating the NF-κB activation, so as to inhibit the development of OA. LJT reversed the progression of OA by inhibiting inflammation, apoptosis and senescence in animal models and chondrocytes. The effects of LJT are mediated through the STING/NF-κB pathway. [Display omitted] •LJT reversed the progression of OA in mice.•LJT alleviated chondrocyte ECM degradation both in vitro and in vivo.•LJT inhibits chondrocyte apoptosis, senescence and inflammation in osteoarthritis.•The anti-osteoarthritis effect of LJT is mediated by inhibiting the activation of STING.•LJT inhibits OA progression through modulating the STING/NF-κB signaling axis.